2012
DOI: 10.1128/jvi.00147-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Priming with H1N1 Influenza Viruses of Variable Antigenic Distances on Challenge with 2009 Pandemic H1N1 Virus

Abstract: Compared to seasonal influenza viruses, the 2009 pandemic H1N1 (pH1N1) virus caused greater morbidity and mortality in children and young adults. People over 60 years of age showed a higher prevalence of cross-reactive pH1N1 antibodies, suggesting that they were previously exposed to an influenza virus or vaccine that was antigenically related to the pH1N1 virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Previous exposure to seasonal influenza viruses, even decades in the past, may provide partial immunity to diverse and emerging influenza virus strains in humans (23,51). This concept is supported by a recent study by O'Donnell et al, who measured protection provided by antigenically distant seasonal H1N1 influenza virus strains against pandemic influenza virus challenge in ferrets (23).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous exposure to seasonal influenza viruses, even decades in the past, may provide partial immunity to diverse and emerging influenza virus strains in humans (23,51). This concept is supported by a recent study by O'Donnell et al, who measured protection provided by antigenically distant seasonal H1N1 influenza virus strains against pandemic influenza virus challenge in ferrets (23).…”
Section: Discussionmentioning
confidence: 89%
“…There is circumstantial evidence from human studies and animal models that T cells recognizing conserved epitopes can mediate heterotypic immunity against divergent influenza virus strains in the absence of crossreactive NAbs (15)(16)(17)(18)(19)(20)(21)(22), though this concept has so far been tested directly only in mice (21). Accordingly, a number of studies have suggested that infection with seasonal influenza virus provides a level of protection against the swine-origin pandemic 2009 influenza virus (H1N1pdm) in the absence of NAbs, an effect which may be mediated by cross-reactive T cell responses (17,(23)(24)(25)(26)(27)(28). However, the degree to which T cells can mediate effective, longlived heterotypic immunity to influenza in humans remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that of the individuals .45 y of age with undetectable HI titers to A(H1N1) pdm09, nearly all (28/31, 90%) had ADCC-mediating Abs to the A(H1N1)pdm09 virus prior to the 2009 pandemic (44). Numerous animal studies showed that infection with seasonal H1N1 viruses, particularly with H1N1 viruses circulating pre-1960, can provide a level of protection from severe A (H1N1)pdm09 virus infection (21,(60)(61)(62)(63). In studies in which Nabs against A(H1N1)pdm09 could not be detected, the levels of nonneutralizing binding Abs correlated closely with protection from severe A(H1N1)pdm09 infection (12,61).…”
Section: The Influence Of Influenza Adcc-mediating Abs On the 2009 Pamentioning
confidence: 99%
“…Numerous animal studies showed that infection with seasonal H1N1 viruses, particularly with H1N1 viruses circulating pre-1960, can provide a level of protection from severe A (H1N1)pdm09 virus infection (21,(60)(61)(62)(63). In studies in which Nabs against A(H1N1)pdm09 could not be detected, the levels of nonneutralizing binding Abs correlated closely with protection from severe A(H1N1)pdm09 infection (12,61). Indeed, our studies showed that previous infection of macaques with seasonal H1N1 virus induced cross-reactive ADCCmediating Abs toward A(H1N1)pdm09 (43).…”
Section: The Influence Of Influenza Adcc-mediating Abs On the 2009 Pamentioning
confidence: 99%